Speciation in fractured rock landforms: towards understanding the diversity of subterranean cockroaches (Dictyoptera: Nocticolidae: Nocticola) in Western Australia - Trotter, Andrew J.; Mcrae, Jane M.; Main, Dean C.; Finston, Terrie L. (Zootaxa, 2017)
Three new species of subterranean cockroach of the genus Nocticola from the Pilbara region of Western Australia are described on morphological characters of males. Nocticola quartermainei n. sp., Nocticola cockingi n. sp. and Nocticola currani n. sp. occur in fractured rock landforms and have varying degrees of troglomorphies. Sequence divergence of mitochondrial cytochrome c oxidase subunit I (COXI) clearly demonstrated populations are reproductively isolated over very short distances for the highly troglomorphic Nocticola cockingi n. sp. and Nocticola currani n. sp. and conversely, there is less isolation within the same landforms for the less troglomorphic Nocticola quartermainei n. sp.